Gastric foveolar-type adenomas endoscopically showing a raspberry-like appearance in the Helicobacter pylori-uninfected stomach - Shibagaki, Kotaro; Fukuyama, Chika; Mikami, Hironobu; Izumi, Daisuke; Yamashita, Noritsugu; Mishiro, Tsuyoshi; Oshima, Naoki; Ishimura, Norihisa; Sato, Shuichi; Ishihara, Shunji; Nagase, Mamiko; Araki, Asuka; Ishikawa, Noriyoshi; Maruyama, Riruke; Kushima, Ryoji; Kinoshita, Yoshikazu (Endoscopy International Open, 2019)
Background and study aims Foveolar-type adenoma is described as a very rare tumor that occurs in individuals without Helicobacter pylori (HP) infection and diagnosed as adenocarcinoma in the Japanese Classification of Gastric Carcinoma (JCGC). However, we have frequently encountered patients with foveolar-type adenoma that endoscopically resembles a hyperplastic polyp, suggesting that it has just been overlooked to date. Here, we analyzed clinicopathological characteristics of a special subtype of foveolar-type adenoma showing specific endoscopic findings.Patients and methods From a total of 212 patients with gastric cancer resected during a 22-month period, we enrolled 14 (6.6 %) diagnosed with foveolar-type adenoma (adenocarcinoma in JCGC). HP infection status was determined by eradication history, HP serum IgG antibody level, urea breath test, and endoscopic and histological findings. All lesions were observed using white-light endoscopy and narrow-band imaging with magnification endoscopy (NBIME). Endoscopically resected lesions were histologically examined.Results None of 14 patients had a current or past history of HP infection. All lesions were visualized on non-atrophic gastric mucosa as small reddish protrusions with fine granular surface, showing a raspberry-like appearance. NBIME showed papillary or gyrus-like microstructures with irregular capillary. Lesions were histologically diagnosed as foveolar-type adenoma showing MUC5AC-positive gastric mucin phenotype. Ki-67 was overexpressed (median labeling index 69.9 %, range 28.4 – 92.1 %), though all lesions were an intraepithelial tumor without stromal invasion. p53 over-staining was not seen in any.Conclusions Raspberry-like lesions on non-atrophic gastric mucosa in HP-uninfected individuals should be evaluated for the possibility of a special subtype of foveolar-type adenoma.